A revolution almost beyond expression : Jane Austen's Persuasion - Harris, Jocelyn (University of Delaware Press, 2007)
"To praise Jane Austen's novels only as stylistic masterpieces is to strip them of the historical, cultural, and literary contexts that might otherwise illuminate them. By focusing primarily on the political, historical, satiric, actively intertextual, and deeply sexualized text of Persuasion, the author seeks to reconcile the so-called insignificance of her content with her high canonical status, for Austen's interactions with real and imagined worlds prove her to be innovative, even revolutionary."--Jacket